Analysis of the Effect of Contribution Income, Claims on Tabarru Funds in the Sharia Business Unit of PT. Prudential Life Assurance Indonesia, 2016-2021 - Trian Zulhadi; Arisman Arisman; Hengki Hengki (IAIN Palopo, 2023)
The background of this research is the increase in the number of claims paid by the company so that the large expenditure of company funds has an impact on the tabarru fund reserves. In general, the increasing number of claims paid by the company will have an impact on the tabarru reserve fund, which is feared when contribution income decreases, it indicates that the company's health is getting worse. More expenses than income. The purpose of this study was to determine the effect of Contribution Income and Claims on Tabarru Funds, both partially and simultaneously in the Sharia Business Unit of PT Prudential Life Assurance Indonesia in 2016-2021. This type of research is quantitative research with secondary data types originating from the annual financial reports of the PT Prudential Life Assurance Sharia Business Unit for the period 2016 to 2021 which originate from the company's official website, namely www.prudential.co.id. This research data collection technique uses datatime series with multiple linear regression analysis models to examine the effect of the independent variables on the dependent variable. The results showed that partially Contribution Income has a positive influence on Tabarru Funds with t count (72.09984) positive direction coefficient of 1.079889 with a probability of 0.0000 <t table (0.05). While Claims have a positive influence on Tabarru Funds with t count (2.699611) positive direction coefficient of 0.040033 with probability (0.0165) <0.05. Simultaneously Contribution Income and Claims together have a significant effect on the Tabarru Fund with f count (9534.203) and probability 0.000000 <0.05. The percentage of influence of the independent variables (Revenue Contributions and Claims) on the dependent variable (Tabarru Fund) is 99.9% while the rest is influenced by other variables not included in this research model. The recommendation from the results of this study for companies is to maintain the stability of contribution income by monitoring the smooth payment of participant contributions so that they continue to be active and increase the growth of new participants(new business) as well as being more selective in processing payments for claims submitted by each participant.